Study on the correlation between triglyceride glucose index, triglyceride glucose index to high-density lipoprotein cholesterol ratio, and the risk of diabetes in nonalcoholic fatty liver disease - Sun, Tao; Liu, Jun (Frontiers in Endocrinology, 2025)
BackgroundThis study seeks to investigate the association between the triglyceride-glucose index (TyG), triglyceride glucose index to high-density lipoprotein cholesterol ratio (TyG/HDL-c), and the risk of diabetes in individuals with nonalcoholic fatty liver disease (NAFLD).MethodsThis retrospective study encompassed 457 NAFLD patients from The Central Hospital of Shaoyang, monitored over a three-year period. Missing data were addressed using multiple imputation, and the Synthetic Minority Over-sampling Technique (SMOTE) was employed to balance the dataset. Multicollinearity analysis was conducted to evaluate the collinearity among variables, while principal component analysis was utilized to examine the distribution of variables in both the original and balanced datasets. A multivariate logistic regression model was used to assess the association between TyG, TyG/HDL-c, and the risk of diabetes in NAFLD patients, adjusting for various covariates. Subgroup analysis was performed to identify differences across diverse populations, and restricted cubic splines (RCS) were used to explore potential non-linear relationships. The receiver operating characteristic (ROC) curve examined the diagnostic value of individual and combined indicators in assessing the risk of diabetes in NAFLD patients.ResultsUpon adjustment for all covariates, TyG was found to significantly elevate the risk of diabetes among patients with NAFLD (OR = 1.96, 95% CI: 1.67-2.30, P < 0.001), with a notable non-linear relationship observed (threshold: 2.39, P-nonlinear = 0.002). Similarly, TyG/HDL-c significantly increased diabetes risk (OR = 1.90, 95% CI: 1.60-2.26, P < 0.001), also demonstrating a distinct non-linear association (threshold: 2.20, P-nonlinear < 0.001). Subgroup analyses revealed significant interactions between TyG and TyG/HDL-c across different gender subgroups (P for interaction < 0.05). The ROC curve analysis indicated that the combined use of TyG and TyG/HDL-c provided superior diagnostic performance for assessing diabetes risk in NAFLD patients (Area Under the Curve [AUC]: 0.703, 95% CI: 0.665-0.740), compared to the use of TyG (AUC: 0.694, 95% CI: 0.656-0.732) or TyG/HDL-c (AUC: 0.693, 95% CI: 0.655-0.731) independently.ConclusionBoth TyG and TyG/HDL-c are significantly associated with an increased risk of diabetes in NAFLD patients, exhibiting non-linear relationships. Furthermore, these associations vary significantly across gender subgroups, their combined use enhances risk assessment, supporting their clinical utility in evaluating diabetes risk.